Intra-religious peaceful coexistence in arabic literature: the case of the Jordanian writer Ġālib Halasā (Религиски дијалог и соработка, 2020)
This paper aims to analyze an example of how intrareligious dialogue and peaceful coexistence are dealt with in theArabic novel. It focuses on two works by Jordanian writer ĠālibHalasā, namely the short story Wadīʿ wa-al-qaddīsa Mīlāda waaḫarūn (1968) and the novel Sulṭāna (1989). The purpose of thepaper is to show how such a cohabitation is portrayed by theauthor, coupling a historical and a literary reading, in order to showsome sides of peaceful coexistence in Jordan.While conflict and violence are widely explored issues in thescholarship dealing with Arabic literature, the same is not truefor dialogue and peaceful coexistence. Despite their growingpopularity, Peace studies have not broken through the wall ofArabic literary studies yet.The cliché can be challenged by changing our perspective andhighlighting the role of literature as a bridge between differentfaiths and communities. Moreover, we need to re-think the relationbetween literature and peace not as a secondary corollary of themore familiar literature/war pattern, but as a study subject in itsown right. It is necessary to point out the importance of reflectingon positive peace in modern and contemporary Arabic literature,and to start building a new critical discourse revolving aroundpeacebuilding.